The Impact of COVID-19 on Mental Health and Quality of Life - Nimra Azhar, Madeeha Younas, Samreen Shahzaib, Misbah Waris, Arnab Altaf, Sadaf Waris (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The COVID-19 (Coronavirus Disease of 2019) virus has affected millions of people around the world, and it is likely to induce mental health issues in those who have never had one before, as well as worsen the condition of those who already have. Objective: To determine the effect of COVID-19 on mental health and quality of life. Methodology: The non-probability convenient sampling strategy was utilized in this cross-sectional research. A sample of 300 Males and Female with age above 30 who have gone through COVID-19 and recovered before one month or more are included in the study. All patients who already had cognitive issues even before COVID-19 were excluded from the study. The study variables were measured using the MMSE (mental health) and WHOQOL-BREF (quality of life). Results: The results revealed that 128 participants (43%) of the respondents were male and 172 participants (57%) were female. The findings showed that 32 people were with normal mental health, 100 were with mild and 36 were with moderate mental health between the ages of 30-39. 52 people were with normal mental health, 24 were with mild and no one was with moderate mental health between the ages of 40-49. 4 people were with normal mental health, 4 were with mild and 24 were moderate mental health between the ages of 50-59. 12 people were with normal mental health with, 4 were with mild and no one was with moderate mental health between the ages of 60-69. The results also showed that there was a significant association between mental health and quality of life. chi-square test of independence showed significant association between mental health and quality of life with ꭓ2 (N = 300) = 600.0, p = .000. The findings showed that people with normal mental health had very good quality of life, people with mild mental health have poor quality of life and people with moderate mental health have very poor quality of life. Conclusion: It was concluded from the study that COVID-19 has badly effected mental health and quality of life of the patients suffered from coronavirus. Keywords: COVID-19, Mental Health, Quality of Life, Mental State Examination, Chi-Square